Badminton World Championship stress zones and performance factors: The key to success through log-linear analysis - Valldecabres, R.; Benito, A. M. D.; Losada, J. L.; Casal, C. A. (Journal of Human Sport & Exercise, 2022)
The main purpose was to analyse the frequency and effectiveness of different kind of shots and players` footwork performed by single men badminton players on World Championship depending on court zone. 18 matches were randomly selected and evaluated with a total of 1,273 points and 5,710 play actions. The most stressed court zone is Z5 and Z8 (middle zone) followed by Z10 (deep and lateral zone), while the most successful areas are Z8 (left middle zone) and Z10. When analysing footwork depending on distance covered by players, large footwork is performed mostly to Z1 and Z2. Hitting the shuttlecock with no previous movement is the most common situation from Z4 and Z5. When gathering in three court zones, the most stressed one is middle zone with similar values for Net and deep court zone. On the contrary, the most successfully gathered court zone is deep one, followed by middle and Net zones.